Answer: x = -4.333333333
Step-by-step explanation:
Simplifying
(9x + 5) + -1(6x + -8) = 0
Reorder the terms:
(5 + 9x) + -1(6x + -8) = 0
Remove parenthesis around (5 + 9x)
5 + 9x + -1(6x + -8) = 0
Reorder the terms:
5 + 9x + -1(-8 + 6x) = 0
5 + 9x + (-8 * -1 + 6x * -1) = 0
5 + 9x + (8 + -6x) = 0
Reorder the terms:
5 + 8 + 9x + -6x = 0
Combine like terms: 5 + 8 = 13
13 + 9x + -6x = 0
Combine like terms: 9x + -6x = 3x
13 + 3x = 0
Solving
13 + 3x = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-13' to each side of the equation.
13 + -13 + 3x = 0 + -13
Combine like terms: 13 + -13 = 0
0 + 3x = 0 + -13
3x = 0 + -13
Combine like terms: 0 + -13 = -13
3x = -13
Divide each side by '3'.
x = -4.333333333
Simplifying
x = -4.333333333